2004
DOI: 10.1074/jbc.c400232200
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli DNA Polymerase I (Klenow Fragment) Uses a Hydrogen-bonding Fork from Arg668 to the Primer Terminus and Incoming Deoxynucleotide Triphosphate to Catalyze DNA Replication

Abstract: Interactions between the minor groove of the DNA and DNA polymerases appear to play a major role in the catalysis and fidelity of DNA replication. In particular, Arg 668 of Escherichia coli DNA polymerase I (Klenow fragment) makes a critical contact with the N-3-position of guanine at the primer terminus. We investigated the interaction between Arg 668 and the ring oxygen of the incoming deoxynucleotide triphosphate (dNTP) using a combination of site-specific mutagenesis of the protein and atomic substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 38 publications
5
58
0
2
Order By: Relevance
“…34 The most efficiently extended termini all had a minor groove H-bond acceptor in the primer and a relatively hydrophobic minor groove substituent in the template nucleobase. Biochemical studies of natural DNA have clearly shown that H-bond acceptors in the minor groove of the primer nucleobase facilitate extension; [40][41][42][43] interactions between these functional groups and Kf, particularly H-bonds formed between the minor groove H-bond acceptor of the primer nucleobase, Arg668 of Kf, and the ribosyl oxygen of the incoming dNTP, are necessary for the polymerase to properly orient the primer terminus and the incoming triphosphate for catalysis. 42 We have repeatedly observed the same phenomenon in unnatural scaffolds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The most efficiently extended termini all had a minor groove H-bond acceptor in the primer and a relatively hydrophobic minor groove substituent in the template nucleobase. Biochemical studies of natural DNA have clearly shown that H-bond acceptors in the minor groove of the primer nucleobase facilitate extension; [40][41][42][43] interactions between these functional groups and Kf, particularly H-bonds formed between the minor groove H-bond acceptor of the primer nucleobase, Arg668 of Kf, and the ribosyl oxygen of the incoming dNTP, are necessary for the polymerase to properly orient the primer terminus and the incoming triphosphate for catalysis. 42 We have repeatedly observed the same phenomenon in unnatural scaffolds.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical studies of natural DNA have clearly shown that H-bond acceptors in the minor groove of the primer nucleobase facilitate extension; [40][41][42][43] interactions between these functional groups and Kf, particularly H-bonds formed between the minor groove H-bond acceptor of the primer nucleobase, Arg668 of Kf, and the ribosyl oxygen of the incoming dNTP, are necessary for the polymerase to properly orient the primer terminus and the incoming triphosphate for catalysis. 42 We have repeatedly observed the same phenomenon in unnatural scaffolds. [18][19][20][21][22] Here, this idea is further supported by the significantly decreased efficiency of extension of primers terminating in either dMM3 or dDM5.…”
Section: Discussionmentioning
confidence: 99%
“…The sequences of the oligodeoxynucleotides are shown in Table 1. The primer was 32 P-labeled with [␥-32 P]ATP and annealed with a 20% excess of the template as described previously (32). The P15/T24 substrate was used in all except the pyrophosphorylation experiments and is referred to as the DNA substrate.…”
Section: General-[␥-mentioning
confidence: 99%
“…This reaction was fit to the burst equation to obtain a reduced amplitude of 3.2 Ϯ 0.3 nM. To determine the amount of product that is caused by the rebinding of [␣- 32 P]dCTP in the presence of 1 mM unlabeled dCTP, the experiment described by Fig. 7A (OE) was performed.…”
mentioning
confidence: 99%
See 1 more Smart Citation